Effects of different ratios of soluble to insoluble dietary fiber on growth performance and intestinal health of piglets - Luya Feng; Zhenfu Luo; Jing Wang; Kunfu Wu; Wenliang Wang; Zhimou Liu; Juping Wen; Zhenbin Wang; Gregory J. Duns; Xiaokang Ma; Bi'e Tan (Animal Nutrition, 2024)
This study investigated the impact of different ratios of soluble to insoluble dietary fiber (SDF:IDF) formulations by sugar beet pulp (SBP) supplementation on piglet growth performance, nutrient digestibility, immune function, intestinal morphology, intestinal microbiota and intestinal health. A total of 60 crossbred piglets (Duroc × [Landrace × Yorkshire]) at 40 d old with body weight of 10.0 ± 0.3 kg were randomly assigned to 5 treatments with 6 replicates per treatment and 2 piglets per replicate in a 21-d trial. The dietary treatments included a corn-soybean meal diet (0% SBP supplementation; CON), and diets supplemented with 2%, 4%, 6%, and 8% SBP, representing different SDF:IDF ratios at 10.16%, 13.53%, 16.79%, 19.86%, and 24.81%, respectively. The results indicated that the 8% SBP treatment had a negative effect on feed-to-gain ratio (linear, P = 0.009) compared with the CON treatment (P = 0.021). The apparent total tract digestibility (ATTD) of crude protein was lower in treatments supplemented with SBP (P = 0.002) and showed a linear decrease (P = 0.001), while the ATTD of IDF showed a linear increase (P = 0.037) in four SBP treatments compared to the CON treatment. The 4% SBP treatment increased serum concentrations of triglyceride (quadratic, P = 0.019) and K (linear, P = 0.037), and decreased alanine transaminase concentration (quadratic, P = 0.015) compared with the CON treatment. The concentrations of Cit, Cys, Ile, Leu, Orn, Arg, taurine, urea, 1-methylhistidine, α-aminoadipic acid, α-aminobutyric acid and cystathionine in the 4% SBP treatment were highest among all treatments (P < 0.05). The serum concentrations of interleukin-6, interleukin-8, interleukin-10, transforming growth factor-β, and tumor necrosis factor-α in the 6% SBP treatment were higher than those in the CON treatment (P < 0.05), which also increased mucin-2 and G protein-coupled receptor 41 mRNA expression (P < 0.05) in colonic mucosa compared with the CON treatment and improved the intestinal barrier function. Diets containing more than 19.86% SDF:IDF could impair the intestinal health in piglets when SBP was used as the SDF source. Supplementing nursery piglet diets with 16.79% to 19.86% SDF:IDF is recommended for improving intestinal barrier function, increasing short-chain fatty acids concentrations, and improving intestinal microbiota composition.